" I didn't need to be shy; I participated in the class": A case study of WTC learning support among university students in a remote area - Hasanah, Shofiyatul; Pradipta, Parahita; Efendi, Erfan (JEES (Journal of English Educators Society), 2022)
In language classrooms all around the world educators contest to get students to address in the target language (Yashima, 2018). Educators in University level are steadily attempting new methodology to enhance students with WTC to efficiently speak during teaching-learning process. This qualitative study was designed to investigate the link between students' Willingness to Communicate (WTC) English via Mobile Assisted Language Learning (MALL)by the media supporting devices used in online learning. To gain the data, some interviews to ten lecturers and seven students’ participant have been conducted. the finding revealed that media supporting devices in online learning relate to students' WTC English via MALL such as (a) teaching-learning media flexibility, (b) teaching-learning media clarity, (c) teaching-learning classroom sequence formality, (d) teaching-learning media consistency, then (e) techno pedagogical discernment over lecturers and students. This study necessitates that heightening the WTC teaching-learning capacity via MALL through mobile devices extends substantial learning assistance, predominantly in the concept of efficiency for online classroom activities in real-time concurrences. HIGHLIGHTS: The importance of media supporting factors, including media flexibility, media clarity, formality of class sequence, class consistency, and techno-pedagogical wisdom for lecturers and students. The impact of students' access and proficiency with media support tools on their engagement and success in online learning. Well-equipped students, who have access to devices like laptops or notebooks, are better prepared to use platforms like Zoom and Google Meet. In contrast, students with limited media tools find platforms such as WhatsApp and YouTube more accessible. This study highlights the influence of economic background on students' access to technology and the subsequent impact on their choice of online communication tools.